LARGE BOWEL OBSTRUCTION AND ENDOMETRIOSIS - A.Alshekh, Ahmed; A.Mohammadan, Ahmed (Gezira Journal of Health Sciences, 2005)
A young lady 31 years old, single presented to the surgical emergency with abdominal pain & vomiting for 4 days. Pain was of sudden onset poorly localized, but server & continuos. It was associated with vomiting and absolute constipation. There was burning micturition, but no changes of colour or increased frequently. No pain or bleeding per rectum. Her menarche was at 14, kata 6/30, regular with dysmenorrhoea, otherwise normal. The patient looked ill, not pale and was febrile. Pulse was 120/min, respiratory rate 30/min. Chest, cardiovascular and central nervous systems were normal. Abdominal examination showed distended, tender abdomen all over with guarding and was resonant on percussion. Bowel sound were heard. Per rectal examination revealed a high upper rectal mass just touched by the tip of the finger. The mucosa over it was smooth and intact. The rectum was empty. No mucus or blood in the examining finger. The provisional diagnosis of large bowel obstruction due to tumor(?Malignant) was suggested and intussusception was put as a differential diagnosis. The investigations done were: Hemoglobin was 84%, urine showed a trace of protein no red blood cells, serum potassium was 2.5 mmol/L, sodium was 126 mmol/L. X ray abdomen showed distended bowel. The patient was resuscitated and prepared for laparotomy. Under general anesthesia, a lower- mid line incision was made extended above the umbilicus and the abdomen opened. There was distended transverse, and ascending colon and coecum. Small bowel not distended. A very hard mass felt in the upper rectum firmly fixed and inseparable from the uterus. The suspected diagnosis was rectosigmoid carcinoma, otherwise the abdomen was normal. Loop transverse colostomy was made and a biopsy was taken. The patient smoothly from anasethia. The postoperative course was uneventful.